The Hardiness Profile of Islamic Boarding School Student in Indonesian - Ummah Karimah; Yusuf Syamsu; Nurihsan Juntika; Budiman Nandang (STAI Hubbulwathan Duri, 2021)
The primary goal of this study is to evaluate the hardiness profile of students in Islamic boarding schools and determine whether or not hardiness has a practical impact on students through Islamic boarding schools, with the top indicators being challenge, control, and commitment. Every shift brings with it a new set of challenges, which can be challenging to adjust to. This research employs quantitative methods to demonstrate this. For the 2020/2021 academic year, student boarding school students in Jakarta served as the study's subject population. As a result, 76 participants were chosen at random using a purposive selection method. It is possible to get data using the santri hardiness instrument as the method of gathering information. The hypothetical mean approach is utilized in this study to determine the optimal score, the minimal score, the standard deviation, and the theoretical mean. The score range is obtained in order to determine the category, which will be as follows: X 129.3 indicates a high category, 103.7 129.3 indicates a medium category, and X 103.7 indicates a low category. It is possible to conclude from these estimates that the hardiness profile of boarding school kids falls into the middle category. The result is that most students have attitudes and skills that are not yet optimal for coping with life difficulties in Islamic boarding schools.